Aspectos populacionais do caranguejo-aranha Acanthonyx scutiformis (Dana 1851) (Crustacea, Majoidea, Epialtidae) associado às algas de costões rochosos no sudeste do Brasil - Teixeira, Gustavo Monteiro [UNESP] (2009)
Acanthonyx scutiformis, an endemic species in the Brazilian coast, is commonly found in intertidal rocky-shore algal communities. This study analyzes the population biology of A. scutiformis from Ubatuba region. A total of 371 specimens were collected over one year. Size range was 4.2-12.7 mm CW (carapace width) for females and 3.7-15.8 mm CW for males. Females predominated in intermediate size classes, whereas males prevailed in the largest ones. The estimated size when 50% crabs were mature was 10.7 mm CW for males and 8.9 mm CW for females. Sex ratio varied among the demographic groups. The processes that influence A. scutiformis population structure can be related to the different times males and females reach sexual maturity and probably to the distinct predation pressures on each sex during the adult phase.